Lensometry by two-laser holography with photorefractive Bi12TiO20 - Barbosa, Eduardo A. [UNESP]; Preto, Andre O. [UNESP]; Wetter, NU; Frejlich, J (American Institute of Physics (AIP), 2008)
Refractive and profilometric measurements of lenses were performed through holography with a photorefractive Bi12TiO20 crystal as the recording medium. Two properly aligned diode lasers emitting in the red region were employed as light sources. Both lasers were tuned in order to provide millimetiie and sub-millimetric synthetic wavelengths. The surfaces of the test lens were covered by a 25-mu m opaque plastic tape in order to allow the lens profilometry upon illuminating them with a collimated beam. The resulting holographic images appear covered by interference fringes corresponding to the wavefront geometry of the wave scattered by the lens. For refractive index measurement a diffusely scattering flat surface was positioned behind the uncovered lens which was also illuminated by a plane wave. The resulting contour interferogram describes the form of the wavefront after the beam traveled back and forth through the lens. The fringe quantitative evaluation was carried out through the four-stepping technique and the resulting phase map and the Branch-cut method was employed for phase unwrapping. The only non-optical procedure for lens characterization was the thickness measurement, made by a dial caliper. Exact ray tracing calculation was performed in order to establish a relation between the output wavefront geometry and the lens parameters like radii of curvature, thickness and refractive index. By quantitatively comparing the theoretical wavefront geometry with the experimental results relative uncertainties bellow 3% for refractive index and 1 % for focal length were obtained.